Analisis Kompensasi Dalam Meningkatkan Kinerja Karyawan Pada Hotel Stefani Syariah Pekanbaru - Zulkifli, Zulkifli; Saskia, Nanda (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2022)
Compensation is all forms of giving by the company to its employees in the form of money, goods, or the state of facilities in return for their work. Hotel Stefani Syariah Pekanbaru provides compensation in the form of financial compensation and non-financial compensation to its employees; this aims to meet the needs of its employees so that employees feel satisfied and are expected to improve their performance. This study aims to analyze compensation in enhancing employee performance. The method in this study is descriptive qualitative analysis, namely analyzing, describing, and summarizing various conditions and situations from multiple data collected either in the form of interviews or observations about the problems studied that occur in the field. The results of this study are based on the results of interviews and analysis of compensation in improving employee performance at Hotel Stefani Syariah Pekanbaru, which is related to financial compensation and non-financial compensation to enhance employee performance. Thus, the initial assumption of some employees who complain that the compensation they receive is not satisfactory is not entirely correct because it is contrary to the results of interviews, which show a positive impact, which means that employees are satisfied with the compensation they receive.